Patients’ Health Records Management in Ugandan Hospitals: A Case of Kabale Regional Referral Hospital - Daniel, Nabimanya; Richard, Sembatya; Ambrose, Atuhaire; Mbabazi, Businge Phelix (International Journal for e-Learning Security (IJeLS, 2020)
Personal health record (PHR) is considered as an emerging patient-centric model of health information exchange, where people can share their health information to other people, however most health facilities in Uganda have not yet adopted it. The study investigated the patients’ health record management at Kabale Regional Referral Hospital. The researcher interviewed fifty (50) Interviewees and data was analyzed using NVIVO version 11.The findings revealed that 88% of the total interviewees express the need for their information to be kept secret from untrusted parties while 12% of the total interviewees didn’t express the need for their information secrecy from untrusted parties. When asked what they feel about what should be done to stop information disclosure to untrusted parties , 20% of the Interviewees expressed concern for keeping their information in closed rooms, 60% of the Interviewees expressed concern for information storage in the computer with passwords and 20% of the respondents expressed concern for hiring external authorities to store their information. The study concluded that privacy of patients’ records was vital to the patients and recommended that security measures be implemented.
Keywords: Healthcare; Patients’ Health Records Management; Ugandan Hospitals; Health Information